Rhinocerebral zygomycosis in a diabetic patient - Mirella Alves da Cunha; Andréia Ferreira Nery; Francisco Pignataro Lima; José Diniz Junior; José Maciel Neto; Nicácia Barbosa Calado; Kleber Giovanni Luz; Eveline Pipolo Milan (Revista da Sociedade Brasileira de Medicina Tropical, 2011)
Rhinocerebral zygomycosis is the most frequent form of fungal infection caused by members of the Zygomycetes class. A fatal case of rhinocerebral zygomycosis caused by Rhizopus (oryzae) arrhizus with histopathological and mycological diagnosis is reported in a diabetic patient.